Palladium-catalyzed intermolecular heck-type reaction of epoxides - Teng, Shenghan (2020)
The palladium-catalyzed intermolecular Heck-type reaction of both cyclic and acyclic epoxides is reported with tolerance of typical polar groups and acidic protons. Suitable alkenes include styrenes, conjugate dienes, and some electron-deficient olefins. In reactions of aliphatic terminal epoxides, ring opening occurs selectively at terminal positions, and stereocenters of epoxides are fully retained. Mechanistic studies provide evidence for in situ conversion of epoxides to β-halohydrins, generation of alkyl radicals, and radical addition to alkenes as key steps. Cyclovoltammetric determination of reduction potentials suggests that during activation of alkyl iodides by palladium(0) complexes, inner-sphere halogen abstraction is more likely than outer-sphere single electron transfer.